NATURAL POLYMER OF TAMARIND SEED: A PROSPECTIVE CARRIER FOR OCULAR DRUG DELIVERY - Sahoo, Rashmirekha; Sahoo, Soumendra (European Scientific Journal, ESJ, 2015)
Natural polysaccharide-based biomaterials are currently being explored as novel drug delivery devices. Important properties of the polysaccharides include controlled biological activity and biodegradability. The tamarind seed is a by-product of the tamarind industry. The decorticated flour, known as tamarind kernel powder has been tried for various biomedical applications such as drug delivery carriers. The xyloglucan component of it, a hemicellulose, was found to be a biocompatible, non-toxic and cheap agro-based material that could be used safely for controlled drug delivery systems. Studies with tamarind-seed polysaccharide nanocomposites have been conducted, where tamarind and polyvinyl alcohol were blended with Cloisite 30B solution in different ratios showing a sustained delivery of drugs. We certainly foresee the prospect of bioadhesive carriers, such as muco-adhesive polymers of tamarind-seed polysaccharides an effective solution of achieving bioavailability of various ocular drugs when used as topical preparations